Antenatal detection of facial clefts: is the FASP target achievable?. (18th April 2012) - Budd, J; Elsenoun, G Abou; Mousa, HA; Draper, ES
Abstract : Background: In 2010 the NHS Fetal Anomaly Screening Programme issued national guidelines and standards concerning the 18 +0 –21 +6 Fetal Anomaly Scan. Cleft Lip +/- Palate (CL+/-P) is one of eleven congenital anomalies now monitored nationally, with a target rate for antenatal diagnosis of 75%. Here we present antenatal detection rates for CL+/-P in the East Midlands and South Yorkshire Congenital Anomaly Register (EMSYCAR) between 2005-2010 and associated anomalies. Methods: All cases of oro-facial clefts, with dates of delivery between 01/01/200531/12/2010 were identified by EMSYCAR. Cases were coded using the ICD10 system, distinguishing between Q35 (CP), Q36 (CL) and Q37 (CL+P). Details of antenatal detection and associated anomalies were recorded. Results: There were 600 cases of oro-facial clefting reported (13.8/10, 000 deliveries (95%ci, 12.7-14.9): 403 were cases of CL (n=134) or CL+P (n=269). This rate, 9.3/10, 000 (95%ci, 8.4-10.2), is virtually identical to the EUROCAT surveillance system (9.36). 70% (95%ci, 65%-75%) of cases (283/403) were diagnosed antenatally. However, this figure was significantly lower for CLs (57%;95%ci, 49%-66%) than forCL+P cases (76.5%;95%ci, 71%-82%). Although antenatal detection rates are improving, from 66% (95%ci, 59%-73%) in 2005-2007 to 77% (95%ci, 68-80%) in 2008-2010, this was not quite statistically significant (p=0.07). There is also wide variation in detection rates between individual trusts (range 46%-100%) 76% of CL cases were isolated: 8.2% with chromosomal and 13.4% multiple aetiology. Rates for CL+P were 71.7%, 10.8% and 15.2%, respectively. Conclusions: The FASP target of 75% for CL+/-P is being achieved across EMSYCAR. Approximately one quarter of CL+/-P cases are associated with other anomalies.